The Influence of Psychological (Mental) Training to Improve the Performance of Football - Asep Angga Permadi; Herman Subarjah; Dikdik Zafar Sidik; Nuryadi Nuryadi (STKIP Muhammadiyah Kuningan, 2021)
This research is aimed to identify the experiment of psychological training on football players to improve their performance. The method used in this research is experimental. This research participant is two football teams, namely Persigar and Porda Garut, consisting of 46 football players. The instrument in this research is Mental Skills Test-football (MST-f) and Evaluation Football Performance. The results revealed that the implementation of psychological training is affected, performance players. That means there is a significant relationship between psychology and football performance. The experimental group's psychological test results (Porda Garut) showed an average score of 3.75 points, those higher than the control group (Persigar Garut), which had an average score of 3.16 points. The experimental group's performance test (Porda Garut) had a higher increase of 73.11%, while the control group (Persigar Garut) experienced a lower growth of 15.54%. This research concludes that psychological training can be implemented in football training as well.